TEKANAN SOSIAL PERTANYAAN "KAPAN NIKAH?" DAN DAMPAKNYA TERHADAP MINAT MENIKAH REMAJA QUARTER AGE - Novrilia Indah Sari; Irawan, Deni (Jurnal Studia Insania, 2025)
The question "When will you get married?" is a common social phenomenon in Indonesia, often causing psychological pressure on individuals in their quarter age. This study aims to analyze two aspects: how this question is perceived by young adults and its impact on their interest in marriage. Some individuals see it as a form of social concern, while others perceive it as intrusive and stressful. Using a qualitative case study method, data were collected through semi-structured interviews with purposively selected informants. The findings show that while some respondents feel encouraged to marry, others experience anxiety and decreased interest due to societal expectations. These results highlight the importance of understanding the psychological impact of this question and promoting more empathetic communication to reduce unnecessary pressure.